Pengembangan media pembelajaran berbasis PPT interaktif muatan pembelajaran IPS pada siswa kelas V SD Negeri Bangunharjo Sewon Bantul - Femi; Endah Marwanti; Arya Dani Setyawan; Eka Ridha Nofrida (Universitas Sarjanawiyata Tamansiswa, 2023)
This study aims to, (1) develop products in the form of interactive PPT-based learning media on social studies learning on the material of Dutch colonization in Indonesia grade V SD Negeri Bangunharjo Sewon Bantul, and (2) test the feasibility of interactive PPT-based learning media on social studies learning in grade V students of SD Negeri Bangunharjo Sewon Bantul.The research method used is the development research method (Research & Development or R&D) which consists of 6 stages, namely: potential and problems, data collection, product design, product validation, design revision, and limited trial. In the sample of this study, researchers took grade V students totaling 6 people. Data collection techniques using documentation, semi-structured interviews, and observation. Validation of Interactive PPT learning media is given to two validators, namely material and media experts to determine the validity of the products developed. Student response questionnaires were given to students to determine the quality of Interactive PPT-based learning media. The data were analyzed using quantitative data analysis techniques. The results showed that (1) Interactive PPT-based learning media for grade V social studies content on the material of Dutch colonization in Indonesia has an Interactive PPT-based learning media development process (2) Interactive PPT-based learning media teaching materials obtained a feasibility percentage of 84% material experts with very feasible criteria, while from media experts obtained a feasibility percentage of 92% with very feasible criteria. Student responses from the limited trial obtained a percentage of 95.33% with very feasible criteria. So, it can be concluded that Interactive PPT-based learning media on grade V social studies content is very feasible to use as teaching material in the learning process, and is very well used during the learning process.